2003
DOI: 10.5191/jiaee.2003.10304
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Knowledge and Attitudes about International Agricultural Issues

Abstract: The purpose of this study was to determine agricultural education undergraduates '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 12 publications
(26 reference statements)
2
40
0
Order By: Relevance
“…This study design was causalcomparative; which is used to identify cause and effect relations, with the critical feature of an independent categorical variable (Gall, Gall, & Borg, 2007). To evaluate students' knowledge and attitudes toward global agricultural issues and their attitudes to engage in society as global citizens, we used modified versions of the International Agricultural Awareness and Understanding survey instrument by Wingenbach et al (2003) and Hurst (2013), and the Global Citizenship Scale by Morais and Ogden (2011). Knowledge items that were outdated were replaced with others addressing the main issues highlighted by the Food and Agriculture Organization of the United Nations (FAO) in 2014, in the post-2015 development agenda, and the Millennium Development Goals (MDG).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study design was causalcomparative; which is used to identify cause and effect relations, with the critical feature of an independent categorical variable (Gall, Gall, & Borg, 2007). To evaluate students' knowledge and attitudes toward global agricultural issues and their attitudes to engage in society as global citizens, we used modified versions of the International Agricultural Awareness and Understanding survey instrument by Wingenbach et al (2003) and Hurst (2013), and the Global Citizenship Scale by Morais and Ogden (2011). Knowledge items that were outdated were replaced with others addressing the main issues highlighted by the Food and Agriculture Organization of the United Nations (FAO) in 2014, in the post-2015 development agenda, and the Millennium Development Goals (MDG).…”
Section: Methodsmentioning
confidence: 99%
“…Elting (2001) recommended the undergraduate education curriculum in agricultural sciences should aim to prepare aware and knowledgeable students for a global context. Additionally, Wingenbach et al (2003) suggested an agricultural curriculum needed to expand students' knowledge of international agriculture issues and understanding of "policies, products, people, and cultures to prepared students for their careers (2003). Furthermore, an adequate internationalization of the agricultural curriculum will most likely foster positive attitudinal change in students, thus increasing their international awareness (Moriba, Edwards, Robinson, Cartmell, & Henneberry, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Colleges of agriculture in Iran should provide opportunities for students to gain international experience. This is an important implication because global competency is becoming increasingly more important in the competitive global market, and university and colleges are addressing the need for global competency by adding international learning experiences to their curricula (King & Martin, 1995;Hossain, et al, 1995;Bruening & Frick, 2004;Wingenbach, et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing the importance of understanding the global world in which we live and a call for an increase in international exposure for agriculture students is not new. Multiple studies (Connors, 2004;Harder, Lamm, Roberts, Navarro, & Ricketts, 2012;Hunter, 2004;Wingenbach et al, 2003;Zhai & Scheer, 2004) have reported the need for students to gain international experience. Wingenbach et al (2003) conveyed a need for providing "out-of-country learning experiences" (p. 25) for college students given study findings that revealed inadequate knowledge about international agricultural issues.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies (Connors, 2004;Harder, Lamm, Roberts, Navarro, & Ricketts, 2012;Hunter, 2004;Wingenbach et al, 2003;Zhai & Scheer, 2004) have reported the need for students to gain international experience. Wingenbach et al (2003) conveyed a need for providing "out-of-country learning experiences" (p. 25) for college students given study findings that revealed inadequate knowledge about international agricultural issues. Connors (2004) reported undergraduate students had not received exposure or instruction about international 1 agriculture in high school and called for an increase in exposure to international agriculture in both secondary and post-secondary educational programs.…”
Section: Introductionmentioning
confidence: 99%